USE OF MODULE IN LEARNING GUIDELINESTO IMPROVE STUDENT LEARNING OUTCOMES - Ari Metalin Ika Puspita; Agus Budi Santosa (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2018)
This study aims to determine the improvement of students' learning outcomes in the third grade of elementary school in the use of modules on tutoring in SDN IV Tanggung in Tulungagung District. The study design uses a classroom action research consisting of two cycles. Each silklus consists of 4 stages, namely the stage of planning, implementation, observation, and reflection. The subjects of this study are class III students who numbered 42 students in SDN IV Tanggung. Data on the use of Module taken from the observation and interview. The data have been analyzed using qualitative descriptive analysis. The results of this study using module ni indicate that can improve student learning outcomes. Before using student learning result module shows percentage 50% in cycles I and At Cycle II reach 71,69%%. Based on the observations during the implementation of the action on the cycle I and cycle II found the results showed an increase in some aspects specified in this study.